Roles of Interferons in Pregnant Women with Dengue Infection: Protective or Dangerous Factors. (7th September 2017) - Zhang, Hao; He, Zhiyi; Zeng, Wenting; Peng, Hong-Juan
Abstract : Dengue infection is a serious public health problem in tropical and subtropical areas. With the recent outbreaks of Zika disease and its reported correlation with microcephaly, the large number of pregnancies with dengue infection has become a serious concern. This review describes the epidemiological characteristics of pregnancy with dengue and the initial immune response to dengue infection, especially in IFNs production in this group of patients. Dengue is much more prevalent in pregnant women compared with other populations. The severity of dengue is correlated with the level of IFNs, while the serum IFN level must be sufficiently high to maintain the pregnancy and to inhibit virus replication.